PENGARUH KOMPOS KULIT DURIAN DAN NPK ORGANIK TERHADAP PRODUKSI TANAMAN PARE (Momordica charantia L.) - Okriyanto; Siti Zahrah; Saripah Ulpah (UIR Press, 2023)
The Effect of Compost Durian Peel and Organic NPK on the Production of Bitter Gourd (Momordica charantia L)”. The purpose of this study was to determine the interaction effect as well as the main effect of durian rind compost and organic NPK on bitter melon production. The research was carried out on the agricultural land of the Food Crops Seed Center, Kuantan Singingi Regency, Jalan Perintis Kemerdekaan KM 2, Pulau Godang Village, Kuantan Tengah District, Kuantan Singingi Regency. The study was conducted for 4 months, from December to March 2023. This study used a factorial Completely Randomized Design consisting of 2 factors, namely the first factor of durian peel compost (K) consisting of 4 treatment levels, namely 0, 1, 2 and 3 kg per plot. The second factor was the dose of Organic NPK (N) which consisted of 4 treatment levels, namely 0, 5, 10 and 15 gram plants. Parameters observed were flowering age, harvesting age, number of fruit per plant, fruit weight per plant, fruit weight per fruit, largest fruit diameter, longest fruit length and number of remaining fruit. Observational data were analyzed statistically and continued with the BNJ test at the 5% level. The results showed that the interaction of durian rind compost and Organic NPK significantly affected the parameters of flowering age, harvesting age, number of fruits per plant, fruit weight per plant, fruit weight per fruit and longest fruit length. The best treatment was a dose of 3 kg of durian peel compost per plot and 15 grams of organic NPK per plant. The main effect of real durian peel compost on all observation parameters. The best treatment is durian peel compost at a dose of 3 kg per plot. The main effect of real organic NPK on all observation parameters. The best treatment is Organic NPK with a dose of 15 grams per plant.